The Pragmatics of Straw Man Fallacies: An Experimental Approach - Schumann, Jennifer; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This open-access book provides the first experimental pragmatic investigation of the straw man, uncovering a variety of factors that increase or decrease the acceptability of this fallacy. The book starts with an overview of the primarily theoretical frameworks on argumentation/fallacies and the straw man. The aim is to provide a synthetic review of the research conducted in argumentation and the study of fallacies with a strong focus on modern approaches and the role of language within these approaches. It is followed by an overview of the empirical methods in argumentation, which leads the reader to the core part of the book, i.e., the experimental pragmatic approach to the straw man fallacy. This part of the book presents several original studies assessing the role of different linguistic factors in the perception of straw men. The book is structured as follows: Chapter 1 introduces the book. The reader will be familiarised with the topic of the straw man as a fallacious argument and the research axes of the book. Chapter 2 provides an overview of argumentation and fallacy theory, and the role of language in the selected approaches. Chapter 3 discusses various theoretical approaches to the straw man fallacy. Chapter 4 provides an overview of empirical methodologies in argumentation. Chapter 5 presents a series of exploratory studies discussing three pragmatic factors. Chapter 6 addresses the question of information structure for the communication of straw man fallacies. Chapter 7 presents a more detailed analysis of the role of causal connectives used to introduce an argument. Chapter 8 presents a cross-linguistic examination of the role of causal connectives with attributive functions. Chapter 9 focuses on the refutational dimension of the straw man fallacy. The previous chapters have mainly investigated factors related to the misrepresentational dimension of the straw man. Chapter 10 provides a summary of the main findings and opens toward future lines of investigation. The book targets young and senior scholars interested in research on straw man fallacies, experimental approaches to the study of fallacies and argumentation in general.
Introduction -- State of the Art: Argumentation and Fallacy Theory -- The Straw Man Fallacy -- Exploratory Studies on the Straw Man Fallacy -- The Role of Information Structure -- The Role of Connectives for Straw Man Fallacies -- A Cross-Linguistic Approach to Assess the Role of Connectives for Straw Man Fallacies -- The Refutational Dimension of the Straw Man -- Conclusion -- References.
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Logic; Philosophy; Methodology; Reasoning; Logic; Experimental Philosophy; Informal Logic